A COVID-19 nosocomial cluster in a university hospital in southern Italy: a social network analysis - Bianchi, F. P.; Stefanizzi, P.; Migliore, G.; Melpignano, L.; Dalneo, A.; Vimercati, L.; Marra, M.; Working Group, CR; Tafuri, S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. Healthcare workers on duty at the hospital are at high risk of COVID-19 infection. However, despite the introduction of risk-lowering practices in the hospital setting, there have been many cases of SARS-COV-2 infection among Health Care Workers. Fast and efficient contact tracing and Sars-CoV-2 PCR-based testing of the close contacts of Health Care Workers with confirmed infections are essential steps to limit nosocomial outbreaks. Methods. This cross-sectional study was conducted at Bari Policlinico General University-Hospital (Apulia, Italy) and describes the management of a cluster of SARS-COV-2 infections in three Operative Units. The contact tracing activities and the measures implemented to control the outbreak are described. Results. Among the 186 Health Care Workers active in the cluster setting, there were 9 (4.8%) confirmed cases, including the index case. Due to the outbreak, three Operative Units were closed to limit virus circulation. Health Care Workers with confirmed infections tested negative after a mean of 28.0±6.6 days (range: 13–37) and none required hospitalization. Conclusions. Protection of the health of Health Care Workers during the COVID-19 pandemic should be a public health priority. However, despite recent recommendations and the implementation of protective measures, SARS-COV-2 infections of Health Care Workers remain at a high rate, indicative of the continued high risk of cluster onset in the nosocomial setting.